2019
DOI: 10.1111/ele.13207
|View full text |Cite
|
Sign up to set email alerts
|

Low siring success of females with an acquired male function illustrates the legacy of sexual dimorphism in constraining the breakdown of dioecy

Abstract: Dioecy has often broken down in flowering plants, yielding functional hermaphroditism. We reasoned that evolutionary transitions from dioecy to functional hermaphroditism must overcome an inertia of sexual dimorphism, because modified males or females will express the opposite sexual function for which their phenotypes have been optimised. We tested this prediction by assessing the siring success of monoecious individuals of the plant Mercurialis annua with an acquired male function but that are phenotypically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 98 publications
(172 reference statements)
0
14
0
Order By: Relevance
“…We also found that F 1 progeny from crosses between the two phenotypes were substantially larger than the non-hybrid progeny. This result may point to heterosis or hybrid vigour, consistent with both parental lineages being inbred (Semel et al , 2006; Hochholdinger and Hoecker, 2007; Wang et al , 2015), and as suggested by the low genetic diversity observed in P+ populations (Santos del Blanco et al , 2019), but also in many P– populations (Obbard et al , 2006b; Pujol et al , 2009, 2010). Alternatively, it is possible that some of the vigour of hybrid individuals is attributable to trade-offs resulting from their lower reproductive effort.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…We also found that F 1 progeny from crosses between the two phenotypes were substantially larger than the non-hybrid progeny. This result may point to heterosis or hybrid vigour, consistent with both parental lineages being inbred (Semel et al , 2006; Hochholdinger and Hoecker, 2007; Wang et al , 2015), and as suggested by the low genetic diversity observed in P+ populations (Santos del Blanco et al , 2019), but also in many P– populations (Obbard et al , 2006b; Pujol et al , 2009, 2010). Alternatively, it is possible that some of the vigour of hybrid individuals is attributable to trade-offs resulting from their lower reproductive effort.…”
Section: Discussionmentioning
confidence: 52%
“…The pedunculate phenotype (labelled ‘P+’), although broadly sympatric with the P– phenotype along the Spanish Mediterranean coastal areas and occupying very similar habitats, occurs rarely in mixed populations with the P– phenotype. A previous study found that the P+ phenotype is substantially better at dispersing pollen than the P– phenotype and enjoys much greater siring success in experimental populations, without any obvious phenotypic advantage to the P– phenotype (Santos del Blanco et al , 2019). One might expect such a superior strategy for pollen dispersal to spread quickly throughout the species range, particularly as it does not appear very costly in terms of other fitness components (Buggs and Pannell, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, whereas the absence of males from a population in the dioecious diploid lineage would be reliably perceived by females in terms of an absence of pollen on their stigmas, or low rates of fertilization of their ovules, monoecious 'females' of the polyploid lineage would receive pollen from other monoecious individuals even when males are absent, which occurs frequently (Pannell et al 2014). Thus, although polyploid monoecious individuals would likely benefit from suppressing the production of male flowers when males are present, because males are so much better at dispersing pollen and outcross siring (Eppley and Pannell 2007a;Santos del Blanco et al 2018), this strategy might be inaccessible to them for want of a suitably reliable signal.…”
Section: Discussionmentioning
confidence: 99%